2011
DOI: 10.1002/ijc.26457
|View full text |Cite
|
Sign up to set email alerts
|

Type and location of tumor‐infiltrating macrophages and lymphatic vessels predict survival of colorectal cancer patients

Abstract: The type of tumor‐infiltrating macrophages may be decisive in tumor immunity, lymphangiogenesis and in the clinical outcome of cancer. Here, we elucidated the prognostic significance of lymphatic vessels, different types of macrophages and the balance between different macrophage types in colorectal cancer. We analyzed the impact of density, type and location of macrophages on the clinical behavior of 159 primary colorectal carcinomas using CD68 as a pan‐macrophage marker and CLEVER‐1/Stabilin‐1 as a marker fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
151
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(157 citation statements)
references
References 39 publications
4
151
2
Order By: Relevance
“…3 and 4, it can be concluded that monocytes represent a potent effector cell population against tumor cells expressing low and high levels of EGFR, whereas PMNs encompass efficient antitumoral capacities only against tumor cells expressing high levels of EGFR. In tumor samples from patients, myeloid cells often constitute the predominant leukocyte tumor infiltrate, particularly if tumors contain necrotic areas (39,41,42). Tumor-promoting and tumor-inhibitory roles have been suggested for both monocytes/macrophages and PMNs based on in vivo studies in mice (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…3 and 4, it can be concluded that monocytes represent a potent effector cell population against tumor cells expressing low and high levels of EGFR, whereas PMNs encompass efficient antitumoral capacities only against tumor cells expressing high levels of EGFR. In tumor samples from patients, myeloid cells often constitute the predominant leukocyte tumor infiltrate, particularly if tumors contain necrotic areas (39,41,42). Tumor-promoting and tumor-inhibitory roles have been suggested for both monocytes/macrophages and PMNs based on in vivo studies in mice (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…In tumor sections, myeloid cells, including tumor-associated macrophages, constitute the major component of the leukocyte tumor infiltrate (27,28); however, their potential role for tumor progression or surveillance is controversial. For example, experiments with cytokine-transfected tumor cells demonstrated inhibitory effects of the recruited myeloid cells on tumor growth (41, 42).…”
Section: Advantages and Disadvantages Of Iga Iso-and Allotypementioning
confidence: 99%
“…For the CD20 antibody rituximab, the innate mononuclear phagocyte network was demonstrated to be the predominant effector cell population in vivo (26). In tumor biopsies, macrophages constitute a major component of the leukocyte infiltrate, where monocyte-derived M0 macrophages are thought to polarize into the tumor-inhibiting M1 or the tumor-promoting M2 phenotypes (27,28). In vitro, both M1 and M2 macrophages phagocytosed human IgG1 antibody opsonized tumor cells (29), but the potential of these subpopulations as effector cells for IgA antibodies has not been investigated previously.…”
mentioning
confidence: 99%
“…The concept of cancer immune-surveillance has been supported by research showing that immune-deficiencies facilitate easy development of a neoplasm, further studies by animal models with inhibition of specific genes coding for the immune response resulted in a higher susceptibility to develop spontaneous or chemically-induced cancers (2,3). Previous studies showed that the infiltration of TAMs in colorectal cancer predicted a good prognosis (4)(5)(6)(7)(8). TAMs have been shown to be highly plastic cells that can display both tumor preventing (M1 macrophages) and tumor promoting functions (M2 macrophages) (9,10).…”
Section: Introductionmentioning
confidence: 99%